The Expression of Virulence Factors in Vibrio anguillarum Is Dually Regulated by Iron Levels and Temperature - Lages, Marta A.; Balado, Miguel; Lemos, Manuel L. (Frontiers in Microbiology, 2019)
Vibrio anguillarum causes a haemorrhagic septicaemia that affects cold- and warm-water adapted fish species. The main goal of this work was to determine the temperature-dependent changes in the virulence factors that could explain the virulence properties of V. anguillarum for fish cultivated at different temperatures. We have found that although the optimal growth temperature is around 25 ºC, the degree of virulence of V. anguillarum RV22 is higher at 15 ºC. To explain this result a RNA-Seq analysis was performed to compare the whole transcriptome profile of V. anguillarum RV22 cultured under low-iron availability at either 25 ºC or 15 ºC, which would mimic the conditions that V. anguillarum finds during colonization of fish cultivated at warm- or cold-water temperatures. The comparative analysis of transcriptomes at high- and low-iron conditions showed profound metabolic adaptations to grow under low-iron. These changes were characterized by a down-regulation of the energetic metabolism and the induction of virulence-related factors like biosynthesis of LPS, production of haemolysins and lysozyme, membrane transport, haeme uptake or production of siderophores. However, the expression pattern of virulence factors under iron limitation showed interesting differences at warm and cold temperatures. Chemotaxis, motility, as well as the T6SS1 genes are expressed at higher levels at 25 ºC than at 15 ºC. By contrast, haemolysin RTX pore-forming toxin, the T6SS2 and the genes associated with exopolysaccharides synthesis were preferentially expressed at 15 ºC. Notably, at this temperature, the siderophore piscibactin system was strongly up-regulated. In contrast, at 25 ºC piscibactin genes were down-regulated and vanchrobactin siderophore system seems to supply all the necessary iron to the cell. The results showed that V. anguillarum adjusts the expression of virulence factors responding to two environmental signals, iron levels and temperature. Thus, the relative relevance of each virulence factor for each fish species could vary depending on the water temperature. The results give clues about the physiological adaptations that allow V. anguillarum to cause infections in different fishes and could be relevant for vaccine development against fish vibriosis.